Investigation of Stress Variation in Push-the-Bit Rotary Steering Bearings Under Weight on Bit and Push Forces - SHEN Bin; YANG Hao; XUE Zhejing; LI Wei; CHENG Feng; LU Lu; WU Jie (Cejing jishu)
As the key component of the push-the-bit rotary steerable system, the accuracy and reliability of the bearing system directly affect the control accuracy and drilling efficiency of the drilling tool on the borehole trajectory. Based on the structural characteristics of the downhole drilling assembly and the motion constraints in the wellbore, the finite element analysis model is established and the bearing system mechanics is analyzed. The maximum equivalent stress of each component of the bearing system and the change rule of its position with the drilling pressure and the thrust force are obtained. The research shows that for the radial bearing and thrust bearing, the maximum equivalent stress position coincides with the loading direction of the thrust force basically. For the bearing friction pair, the maximum equivalent stress position is determined by the loading direction of the thrust force and the contact area between the friction pairs; the change of drilling pressure has more influence on the radial male bearing than on the radial female bearing, and the change of stress on the friction pair of the thrust bearing is more obvious; the change of the thrust force has more influence on the radial bearing and thrust bearing near the bit end than that at the far bit end, and the change of the friction pair stress of the radial bearing is more obvious; with the decrease of drilling pressure or thrust force, the stress distribution of bearing friction pair is more uniform. The research results can provide theoretical support for the maintenance and structure optimization of the push-the-bit rotary steerable system.